PENEGAKAN HUKUM TERHADAP PELANGGARAN HAK CIPTA PEMBAJAKAN SOFTWARE DI INDONESIA - Nuzulia Kumala Sari (Fakultas Hukum Universitas Wahid Hasyim, 2012)
Most of the software circulating in Indonesia is piracy. Software piracy on the market of course is much cheaper price. But this violates Copyright. In 2007, the commercial value of unlicensed software installed on personal computers in Indonesia account for about 7 times greater than the loss in 2003 is 157 million. While in 2009 the losses reached 886 million. In Year 2010, Based on annual data reported by International Data Corporation (IDC) Indonesia ranks 11th of 31 countries with piracy rates of 87 percent in 2010, while the commercial value of pirated software amounting to 1.322 billion. Data from year to year increasing demands for software piracy in Indonesia, the Business Software Alliance (BSA) released the latest statistical data back to the year 2012 on the countries of the world's largest software piracy, and Indonesia are in the order of the seven largest pirate nation. Pirated software on the market of course much cheaper . But this violates Copyright. Law enforcement against the perpetrators of piracy should be a priority at this time.Keywords : Rule of Law, Copyright Infringement, Software Piracy.